(untitled) (Malaysian Management Journal, 1997)
Full execution of EG92 and its impact on intra-EC and international trade are investigated. Theoretical aspects of such integration are analyzed-and a model capturing the trade creation and the trade diversion effect of EC-92 is designed and empirically tested. The implications of the results in terms of intraÂ-EC trade and international trade are pointed out.